Independent Evaluation of IFC's Development Results 2008 : IFC's Additionality in Supporting Private Sector Development - Independent Evaluation Group (Washington, DC : International Finance Corporation, 2012)
The Independent Evaluation of International Finance Corporations (IFC's) Development Results (IEDR) is the annual flagship report of the Independent Evaluation Group (IEG). It reviews IFC's effectiveness in supporting private sector development and its contributions to economic growth and poverty reduction, as well as to environmentally and socially sustainable development. The main purpose of the IEDR is to provide an independent assessment to the Executive Board, IFC Management, and the wider development community about recent trends in IFC's performance, and to stimulate debate and action on IFC strategy and operational processes going forward. The report also serves as a source of knowledge and learning about private sector development, in general, and about development impact, more specifically. This year's IEDR contains two main themes. The first is a review of the development results achieved by IFC-supported operations. On the investment side, this means looking at how well operations that reached early operating maturity during 2005-07 performed, in terms of their financial and economic results relative to specific market benchmarks as well as their environmental and social effects and contributions to private sector development beyond the project. For advisory services, the report presents some emerging results of 293 operations that were closed during 2004-06 and which were evaluated on a pilot basis as part of wider efforts under way to assess performance in this area. The second theme of the report is a preliminary, ex-post look at the 'additionality' or unique role and contribution that IFC brings to its clients through its investment and advisory services operations.